Design and Simulation of a Robot for Hand Rehabilitation based on Wirerope- noose Transmission - Zhang Caihua (Jixie chuandong)
A new novel robot for hand rehabilitation is designed to help patients to do rehabilitation training. Firstly,the human index finger joints are modeled and analysis are conducted on the coupling motion of index finger joints. A combined execute structure of link and joint is proposed,with link structure,the movement interference of adjacent fingers can be avoided and with joint structure,the control way can be simplified. The load on hand is decreased because of the driven module and the execute module are separated by using wirerope- noose transmission as the transmission way for the robot. Then,the 3D model of the rehabilitation robot is designed in Pro / E and the model is imported into ADMAS,and the kinematics analysis is carried out. The simulation results indicate the joints angles are all meet the requirements of index finger for daily movement and the designed structure of the robot is meet the requirements for rehabilitation training. Lastly,the mechanical property of wirerope transmission is analyzed and the calculation formula of tension in wirerope is calculated at arbitrarily space attitude.